Magnetic Strips as Landmarks for Mobile Robot Navigation - Škrabánek, Pavel; Vodička, Pavel (IEEE (Institute of Electrical and Electronics Engineers), 2016)
In this paper, a low-cost localization system designed for mobile robots is introduced. The system has been developed for a teaching aid where a mobile robot operates in a maze. The mobile robot is navigated by a high level control system where path-planning is executed; however, autonomous execution of the plan is required from the robot. The robot uses magnetic landmarks, among others, for its localization. Detection of the landmarks is realized by a triple axis magnetometer sensor. The landmarks are made from a commercially available magnetic sheet. Construction of the magnetic sheets limits this approach. A successful application has to meet some requirements which are described in this paper.
Magnetické pásky jako značky pro navigaci mobilních robotů
Keywords: mobile robots, educational robots, robot sensing systems, magnetic sensors